Service Offshoring, Productivity, and Employment : Evidence from the United States - Amiti, Mary (IMF Working Papers; Working Paper ;, 2005)
This paper estimates the effects of offshoring on productivity in U.S. manufacturing industries between 1992 and 2000, using instrumental variables estimation to address the potential endogeneity of offshoring. It finds that service offshoring has a significant positive effect on productivity in the US, accounting for around 11 percent of productivity growth during this period. Offshoring material inputs also has a positive effect on productivity, but the magnitude is smaller accounting for approximately 5 percent of productivity growth. There is a small negative effect of less than half a percent on employment when industries are finely disaggregated (450 manufacturing industries). However, this affect disappears at more aggregate industry level of 96 industries indicating that there is sufficient growth in demand in other industries within these broadly defined classifications to offset any negative effects.